2015
DOI: 10.1007/s00246-015-1206-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Imaging as a Predictor of Immunoglobulin Resistance in Kawasaki Disease

Abstract: Kawasaki disease (KD) is characterized by myocarditis and left ventricular dysfunction during the acute phase of the illness. Despite treatment with intravenous immunoglobulin (IVIG), a significant number of patients are IVIG resistant. We evaluated KD patients in the acute phase of illness using tissue Doppler imaging (TDI) to assess whether myocardial dysfunction may predict IVIG resistance. All patients with acute KD presenting to Children's Hospital Colorado from February 2007 through March 2014 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Losartan in addition to IVIG suppressed the incidence of the myocarditis. In human, myocarditis and left ventricular dysfunction during acute phase of KD is a predictor of IVIG resistance (18). Thus, our results potentially support that losartan may improve cardiac function by suppressing myocarditis in patients with IVIG-resistant KD.…”
Section: Discussionsupporting
confidence: 60%
“…Losartan in addition to IVIG suppressed the incidence of the myocarditis. In human, myocarditis and left ventricular dysfunction during acute phase of KD is a predictor of IVIG resistance (18). Thus, our results potentially support that losartan may improve cardiac function by suppressing myocarditis in patients with IVIG-resistant KD.…”
Section: Discussionsupporting
confidence: 60%
“…Another additional explanation for the similar LV longitudinal peak systolic ε in recurrent KD and controls may be the small number of children with CALs or IVIG nonresponders, factors that have been associated with decreased LV function. 23) 24) Moreover, as treatment with IVIG has been associated with accelerated recovery of LV function 3) and since all children with KD in our study received IVIG, we could speculate that the decreased LV function caused by myocarditis from repeated recurrences of KD recovered with IVIG treatment.…”
Section: Discussionmentioning
confidence: 73%
“…[15] However, previous literature has demonstrated that African Americans have higher rates of IVIG resistance. [19][20][21] Patients that have IVIG resistance, defined as persistence of fevers after the first dose of IVIG, have been shown to have an increased risk of developing coronary artery abnormalities. [22,23] Further research is needed to determine if racial differences in IVIG resistance have an implication on the development of coronary artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%